ANALISIS PROKSIMAT DAN TOKSISITAS AKUT EKSTRAK DAUN SIRIH MERAH YANG BERPOTENSI SEBAGAI ANTIDIABETES - Mega Safithri; Farah Fahma; Paramitha Wirdani Ningsih Marlina (Jurnal Gizi dan Pangan, 2012)
The aim of this study was to explore the analysis proximate and toxicity of the decoctions of P. crocatum. Fresh leaves of P. crocatum were boiled in water in order to obtain decoction and were examined for its chemical compounds by using SNI 01-2891-1992 method for proximate analysis. Toxicity of decoction extract of P. crocatum was orally fed to rats (Sprague dawley). The results showed that P. crocatum leaves contains 9.27% water, 14.33% ash, 3.96% fat, 22.63% proteins, and 59.08% carbohydrates. Acute toxicity test showed that all rats were still alive after 7 days treatment with P. crocatum decoction for all dose groups (0, 5, 10, and 20 g/kg BB). LC50 value of P. crocatum decoction was 544.82 ppm, meaning that the decoction was relatively harmless and bioactive.